Effect of cardiopulmonary resuscitation training towards cardiac arrest emergency knowledge upon students at Student Health Association of Universitas Gadjah Mada, Indonesia - Achmad, Bayu Fandhi (International Journal of Research in Medical Sciences, 2020)
Background: The cardiovascular disease, especially the sudden cardiac arrest, was the main cause of death and disability throughout the world. The cardiopulmonary resuscitation (CPR) that should be taken by the first responder or witness was an important part in the chain of survival out of the hospital that could improve the prognosis and avoid the rest of the symptoms. Hence, it is important for students to know and possess the skill, especially the cardiopulmonary resuscitation, to handle the emergency situation. University became the appropriate place to organize the CPR training because the students were more conditioned in emotional, social and cultural terms. Methods: This research utilized the quasi-experiment method. The total number of research subject was 56 Universitas Gadjah Mada students at Student Health Association. The implementation of intervention of this research was conducted on 07 July, 2018. The topic in this research intervention were formed based on American Heart Association (AHA) Guideline 2015. Pretest and posttest instrument were 10 multiple choices with five choices of answer. Results: This research proved that the CPR training gave effect on the improvement of the knowledge about emergency situation, particularly the cardiac arrest through cardiopulmonary resuscitation. The pre-test and post-test results showed that there was a knowledge improvement after the training (p=0,000). Conclusions: CPR training could be recommended to have an impact on increasing student knowledge in emergency management, especially cardiac arrest.